A stripped helium star in the potential black hole binary LB-1 - Irrgang, Andreas; Geier, Stephan; Kreuzer, Simon; Pelisoli, Ingrid; Heber, Ulrich (Astronomy & Astrophysics, 2020)
Context. The recently claimed discovery of a massive (M-BH = 68(-13)(+11) M-circle dot) black hole in the Galactic solar neighborhood has led to controversial discussions because it severely challenges our current view of stellar evolution.Aims. A crucial aspect for the determination of the mass of the unseen black hole is the precise nature of its visible companion, the B-type star LSV +22 25. Because stars of different mass can exhibit B-type spectra during the course of their evolution, it is essential to obtain a comprehensive picture of the star to unravel its nature and, thus, its mass.Methods. To this end, we study the spectral energy distribution of LSV +22 25 and perform a quantitative spectroscopic analysis that includes the determination of chemical abundances for He, C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe.Results. Our analysis clearly shows that LSV +22 25 is not an ordinary main sequence B-type star. The derived abundance pattern exhibits heavy imprints of the CNO bi-cycle of hydrogen burning, that is, He and N are strongly enriched at the expense of C and O. Moreover, the elements Mg, Al, Si, S, Ar, and Fe are systematically underabundant when compared to normal main-sequence B-type stars. We suggest that LSV +22 25 is a stripped helium star and discuss two possible formation scenarios. Combining our photometric and spectroscopic results with the Gaia parallax, we infer a stellar mass of 1.1 +/- 0.5 M-circle dot. Based on the binary system's mass function, this yields a minimum mass of 2-3 M-circle dot for the compact companion, which implies that it may not necessarily be a black hole but a massive neutron- or main sequence star.Conclusions. The star LSV +22 25 has become famous for possibly having a very massive black hole companion. However, a closer look reveals that the star itself is a very intriguing object. Further investigations are necessary for complete characterization of this object.
Keywords: stars: abundances; stars: chemically peculiar; stars: early-type; pulsars: individual: LS V+22 25

Hypervelocity stars in the Gaia era Revisiting the most extreme stars from the MMT HVS survey - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (Astronomy & Astrophysics, 2020)
The hypervelocity star (HVS) survey conducted at the Multiple Mirror Telescope (MMT) identified 42 B-type stars in the Galactic halo whose radial velocity in the Galactic rest-frame exceeds +275 km s 1. In order to unravel the nature and origin of those highvelocity outliers, their complete six-dimensional phase space information is needed. To this end, we complemented positions and proper motions from the second data release of Gaia with revised radial velocities and spectrophotometric distances that are based on a reanalysis of the available MMT spectra of 40 objects using state-of-the-art model spectra and a tailored analysis strategy. The resulting position and velocity vectors for 37 stars were then used as input for a subsequent kinematic investigation to obtain as complete a picture as possible. The combination of projected rotational velocity, position in the Kiel diagram, and kinematic properties suggests that all objects in the sample except two (B576, B598) are very likely to be main sequence stars. While the available data are still not precise enough to constrain the place of origin for 19 program stars, we identified eight objects that either come from the outer rim of the Galactic disk or not from the disk at all, along with ten that presumably stem from the Galactic disk. For almost all of those 18 targets with more or less well-constrained spatial origin, the Galactic center (GC) is disqualified as a possible place of origin. The most notable exception is B576, the origin of which coincides extremely well with the GC when assuming a blue horizontal branch nature for it. HVS 22 is by far the most extreme object in the sample. Although its origin is completely unconstrained, an ejection from the GC by the Hills mechanism is the most plausible explanation for its current Galactic rest-frame velocity of 1530(-560)(+690) km s(-1).
Keywords: stars: distances; stars: early-type; stars: fundamental parameters; stars: kinematics and dynamics

Hypervelocity stars in the Gaia era Runaway B stars beyond the velocity limit of classical ejection mechanisms - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich (Astronomy & Astrophysics, 2018)
Context. Young massive stars in the halo are assumed to be runaway stars from the Galactic disk. Possible ejection scenarios are binary supernova ejections (BSE) or dynamical ejections from star clusters (DE). Hypervelocity stars (HVSs) are extreme runaway stars that are potentially unbound from the Galaxy. Powerful acceleration mechanisms such as the tidal disruption of a binary system by a supermassive black hole (SMBH) are required to produce them. Therefore, HVSs are believed to originate in the Galactic center (GC), the only place known to host an SMBH.Aims. The second Gaia data release (DR2) offers the opportunity of studying HVSs in an unprecedented manner. We revisit some of the most interesting high-velocity stars, that is, 15 stars (11 candidate HVSs and 4 radial velocity outliers) for which proper motions with the Hubble Space Telescope. were obtained in the pre-Gaia era, to unravel their origin.Methods. By carrying out kinematic analyses based on revised spectrophotometric distances and proper motions from Gaia DR2, kinematic properties were obtained that help constrain the spatial origins of these stars.Results. Stars that were previously considered (un)bound remain (un)bound in Galactic potentials favored by Gaia DR2 astrometry. For nine stars (five candidate HVSs plus all four radial velocity outliers), the GC can be ruled out as spatial origin at least at 2 sigma confidence level, suggesting that a large portion of the known HVSs are disk runaway stars launched close to or beyond Galactic escape velocities. The fastest star in the sample, HVS 3, is confirmed to originate in the Large Magellanic Cloud.Conclusions. Because the ejection velocities of five of our non-GC stars are close to or above the upper limits predicted for BSE and DE, another powerful dynamical ejection mechanism (e.g., involving massive perturbers such as intermediate-mass black holes) is likely to operate in addition to the three classical scenarios mentioned above.
Keywords: stars: early-type; stars: kinematics and dynamics

PSR J1024-0719: A MILLISECOND PULSAR IN AN UNUSUAL LONG-PERIOD ORBIT - Kaplan, D. L.; Kupfer, Thomas; Nice, David J.; Irrgang, Andreas; Heber, Ulrich; Arzoumanian, Zaven; Beklen, Elif; Crowter, Kathryn; Decesar, Megan E.; Demorest, Paul B.; Dolch, Timothy; Ellis, Justin A.; et al. (Astrophysical Journal, 2016)
PSR J1024-0719 is a millisecond pulsar that was long thought to be isolated. However, puzzling results concerning its velocity, distance, and low rotational period derivative have led to a reexamination of its properties. We present updated radio timing observations along with new and archival optical data which show that PSR J1024-0719 is most likely in a long-period (2-20 kyr) binary system with a low-mass (approximate to 0.4 M-circle dot), low-metallicity (Z approximate to -0.9 dex) main-sequence star. Such a system can explain most of the anomalous properties of this pulsar. We suggest that this system formed through a dynamical exchange in a globular cluster that ejected it into a halo orbit, which is consistent with the low observed metallicity for the stellar companion. Further astrometric and radio timing observations such as measurement of the third period derivative could strongly constrain the range of orbital parameters.
Keywords: binaries: general; pulsars: individual (PSR J1024-0719); stars: distances

quantitative spectral analysis of 14 hypervelocity stars from the MMT survey - Irrgang, Andreas; Kreuzer, Simon; Heber, Ulrich; Brown, W. (Astronomy & Astrophysics, 2018)
Context. Hypervelocity stars (HVSs) travel so fast that they may leave the Galaxy. The tidal disruption of a binary system by the supermassive black hole in the Galactic center is widely assumed to be their ejection mechanism.Aims. To test the hypothesis of an origin in the Galactic center using kinematic investigations, the current space velocities of the HVSs need to be determined. With the advent of Gaia's second data release, accurate radial velocities from spectroscopy are complemented by proper motion measurements of unprecedented quality. Based on a new spectroscopic analysis method, we provide revised distances and stellar ages, both of which are crucial to unravel the nature of the HVSs.Methods. We reanalyzed low-resolution optical spectra of 14 HVSs from the MMT HVS survey using a new grid of synthetic spectra, which account for deviations from local thermodynamic equilibrium, to derive effective temperatures, surface gravities, radial velocities, and projected rotational velocities. Stellar masses, radii, and ages were then determined by comparison with stellar evolutionary models that account for rotation. Finally, these results were combined with photometric measurements to obtain spectroscopic distances.Results. The resulting atmospheric parameters are consistent with those of main sequence stars with masses in the range 2.5-5.0 M-circle dot. The majority of the stars rotate at fast speeds, providing further evidence for their main sequence nature. Stellar ages range from 90 to 400 Myr and distances (with typical 1 sigma-uncertainties of about 10-15%) from 30 to 100 kpc. Except for one object (B 711), which we reclassify as A-type star, all stars are of spectral type B.Conclusions. The spectroscopic distances and stellar ages derived here are key ingredients for upcoming kinematic studies of HVSs based on Gaia proper motions.
Keywords: stars: distances; stars: early-type; stars: fundamental parameters

Runaway blue main-sequence stars at high Galactic latitudes: Target selection with Gaia and spectroscopic identification - Raddi, Roberto; Irrgang, Andreas; Heber, Ulrich; Schneider, David; Kreuzer, Simon (Astronomy & Astrophysics, 2021)
Context. The ESA Gaia mission is a remarkable tool for stellar population analysis through its accurate Hertzsprung-Russell diagram. Its precise astrometry has propelled detailed kinematic studies of the Milky Way and the identification of high-velocity outliers. Aims. Motivated by the historical identification of runaway main-sequence (MS) stars of an early spectral type at high Galactic latitudes, we test the capability of Gaia at identifying new such stars. Methods. We selected ≃2300 sources with Gaia magnitudes of GBP-GRP ≤ 0.05, which are compatible with the colors of lowextinction MS stars that are earlier than a mid-A spectral type, and obtained low-resolution optical spectroscopy for 48 such stars. By performing detailed photometric and spectroscopic analyses, we derived their atmospheric and physical parameters (effective temperature, surface gravity, radial velocity, interstellar reddening, spectrophotometric distance, mass, radius, luminosity, and age). The comparison between spectrophotometric and parallax-based distances enabled us to disentangle the MS candidates from older blue horizontal branch (BHB) candidates. Results.We identify 12 runaway MS candidates, with masses between 2 and 6 M⊙. Their trajectories were traced back to the Galactic disk in order to identify their most recent Galactic plane crossings and the corresponding flight times. All 12 candidates are ejected from the Galactic disk within 2 to 16.5 kpc from the Galactic center and possess flight times that are shorter than their evolutionary ages, which is compatible with a runaway hypothesis. Three MS candidates have ejection velocities exceeding 450 km s-1, thus, they appear to challenge the canonical ejection scenarios for late B-type stars. The fastest star of our sample also has a non-negligible Galactic escape probability if its MS nature can be confirmed.We identify 27 BHB candidates, and the two hottest stars in our sample are rare low-mass stars of late O- A nd early B-types, evolving towards the white dwarf cooling sequence. Conclusions. The combination of Gaia parallaxes and proper motions can lead to the efficient selection of runaway blue MS candidates up to 10 kpc away from the Sun. High resolution spectra are needed to confirm the MS status, via precise measurements of projected rotational velocities and chemical compositions.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: Early-type; Stars: Fundamental parameters; Stars: Horizontal-branch; Stars: Kinematics and dynamics

Spectroscopy of hot subdwarf binaries - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (DE GRUYTER POLAND SP ZOO, 2018)
We present a status report of our spectroscopic analysis of subdwarf binaries consisting of a subdwarf and a F/G/K-type main-sequence companion. These systems selected from SDSS photometry show significant excess in the (infra-)red which can not be explained by interstellar reddening. Inspection of SDSS spectra revealed that most of them are composite spectrum sdB binaries. Once their spectra are disentangled, a detailed spectral analysis can be carried out. It reveals T-eff, log g and the metal abundance of each individual star. The cool companion is of particular interest, because its spectrum reveals the original chemical composition of the binary.

The EREBOS project: Investigating the effect of substellar and low-mass stellar companions on late stellar evolution Survey, target selection, and atmospheric parameters - Schaffenroth, V.; Barlow, B. N.; Geier, S.; Vuckovic, M.; Kilkenny, D.; Wolz, Maximilian; Kupfer, T.; Heber, Ulrich; Drechsel, Horst; Kimeswenger, S.; Marsh, T.; Wolf, M.; et al. (Astronomy & Astrophysics, 2019)
Eclipsing post-common-envelope binaries are highly important for resolving the poorly understood, very short-lived common-envelope phase of stellar evolution. Most hot subdwarfs (sdO/Bs) are the bare helium-burning cores of red giants that have lost almost all of their hydrogen envelope. This mass loss is often triggered by common-envelope interactions with close stellar or even substellar companions. Cool companions to hot subdwarf stars such as late-type stars and brown dwarfs are detectable from characteristic light-curve variations - reflection effects and often eclipses. In the recently published catalog of eclipsing binaries in the Galactic Bulge and in the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey, we discovered 125 new eclipsing systems showing a reflection effect seen by visual inspection of the light curves and using a machine-learning algorithm, in addition to the 36 systems previously discovered by the Optical Gravitational Lesing Experiment (OGLE) team. The Eclipsing Reflection Effect Binaries from Optical Surveys (EREBOS) project aims at analyzing all newly discovered eclipsing binaries of the HW Vir type (hot subdwarf + close, cool companion) based on a spectroscopic and photometric follow up to derive the mass distribution of the companions, constrain the fraction of substellar companions, and determine the minimum mass needed to strip off the red-giant envelope. To constrain the nature of the primary we derived the absolute magnitude and the reduced proper motion of all our targets with the help of the parallaxes and proper motions measured by the Gaia mission and compared those to the Gaia white-dwarf candidate catalog. It was possible to derive the nature of a subset of our targets, for which observed spectra are available, by measuring the atmospheric parameter of the primary, confirming that less than 10% of our systems are not sdO/Bs with cool companions but are white dwarfs or central stars of planetary nebula. This large sample of eclipsing hot subdwarfs with cool companions allowed us to derive a significant period distribution for hot subdwarfs with cool companions for the first time showing that the period distribution is much broader than previously thought and is ideally suited to finding the lowest-mass companions to hot subdwarf stars. The comparison with related binary populations shows that the period distribution of HW Vir systems is very similar to WD+dM systems and central stars of planetary nebula with cool companions. In the future, several new photometric surveys will be carried out, which will further increase the sample of this project, providing the potential to test many aspects of common-envelope theory and binary evolution.
CRIS-Team WoS Importer:2019-10-11